The Impact of E-Commerce on Financial Management and Accounting Strategies In The Digital Age An Applied Study From The Perspective of Faculty Members at Wadi Al-Shati University and Higher Institutes - Taher Abualhasim Jeiballa (Journal of Scientific and Human Dimensions, 2026)
This study aimed to investigate the impact of e-commerce on financial and accounting management strategies in the digital era, focusing on faculty members at Wadi Al-Shatti University and Higher Institutes. Adopting a descriptive-analytical approach, a questionnaire was administered to a sample of academics and experts. The study found that digital transformation necessitates radical changes in financial control and auditing methods, enhancing decision-making efficiency through real-time data accuracy. However, results revealed significant technical and legislative challenges in the local environment hindering full digital integration. The study recommends updating academic curricula and developing information infrastructure to